Dispensasi Pernikahan di Bawah Umur di Kabupaten Tuban - Mohammad, Khaeruddin; Ishaq, Zamroni; Sholihuddin, Sholihuddin (HOKI : Journal of Islamic Family Law, 2023)
Allah SWT has prescribed marriage with the aim of creating a harmonious relationship and relationship boundaries between two people who are considered to have reached their age, but in fact there are marriages that occur even though they are still under the age determined by law. This research is a type of field research with a focus on studying the Juridical-Empirical approach. The judge's considerations at the Tuban Religious Court in granting the request for dispensation for underage marriage in case no. 739/Pdt.P/2021/PA.Tbn. because the judge considers the sociological factors of the child and to prevent something bad happening to the child if they are not married immediately because the child and the child's future husband have been dating for a long time and have loved each other for a long time.